Implementation of the balanced score card as a benches for the performance assessment of Patut Patju Hospital - Linda Azizah; Sastrawan; Sabar Setiawan (Science Midwifery, 2023)
This study aims to test and measure the performance of the Patut Patuh Patju Regional General Hospital in West Lombok using the Balanced Scorecard method. The approach used is mixed-methods research. This study uses secondary data to measure performance based on the four perspectives of the balanced scorecard, namely the financial perspective and the perspective of internal business processes. The population of employees at Patut Patju Hospital in West Lombok is 497 people, and the number of samples to be taken is 100 people. This research was conducted at Patut Patuh Patju General Hospital in West Lombok. After applying the balanced scorecard, the performance of the Patut Patuh Hospital in West Lombok is located in the "sufficient" area because 0.4 lies between 0 and 0.6. Whereas before using the Balanced Scorecard, the hospital's performance was also in the "adequate" area with a value of 0.25, and its financial performance was both in the "less" area with a good value of -1. Performance appraisal using the balanced scorecard provides a more comprehensive picture of the results of the performance assessment, which not only looks at the financial aspects but describes more detailed results regarding the non-financial aspects of the Patut Patuh Patju Hospital in West Lombok, and overall every aspect is in the "good" category.